1991
DOI: 10.1016/0014-5793(91)80362-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the HIV‐1 and HIV‐2 proteinases using oligopeptide substrates representing cleavage sites in Gag and Gag‐Pol polyproteins

Abstract: The xutrx~r~ spa5tkity af rho humn inmunodclicicncy vitua gyp I (HIV-I) unci ~ypc' 2 (HIV-2) pruteimscr ww cumpsrrcl uxiny oli~sprptidcx carreqxMin@ to ckrtveyc aitcx in tha Gqt und Gug4W palyprutcias ur both viruses. All p6lxidcI mimickinp clcavtiyo ailcr MI the junction QT major functiunul pratcin danr;rins were correctly elctivcd by both cnxymcs. Hawuvrr, some athcr peptidcs thought tm reprrwcnt rrcandary cle~ugl: sites rcmiiierd intact. 'Ptrc kin& p:trcttnctcrx (A'* end k,,) abrainrd far the difikranc atbs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
64
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(68 citation statements)
references
References 25 publications
4
64
0
Order By: Relevance
“…Previously, we performed extensive comparisons of the specificities of HIV-1 and HIV-2 proteinases using oligopeptides representing naturally occurring cleavage sites in their Gag and Gag-Pol polyproteins (15). These cleavage sites have been classified as type 1, which contains an aromatic amino acid and Pro at P 1 and P 1 Ј, respectively, and type 2, which has mainly hydrophobic residues but not Pro at the site of cleavage.…”
Section: Substitution Of Amino Acids Of a Type 1 Cleavage Site Peptidmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we performed extensive comparisons of the specificities of HIV-1 and HIV-2 proteinases using oligopeptides representing naturally occurring cleavage sites in their Gag and Gag-Pol polyproteins (15). These cleavage sites have been classified as type 1, which contains an aromatic amino acid and Pro at P 1 and P 1 Ј, respectively, and type 2, which has mainly hydrophobic residues but not Pro at the site of cleavage.…”
Section: Substitution Of Amino Acids Of a Type 1 Cleavage Site Peptidmentioning
confidence: 99%
“…These cleavage sites have been classified as type 1, which contains an aromatic amino acid and Pro at P 1 and P 1 Ј, respectively, and type 2, which has mainly hydrophobic residues but not Pro at the site of cleavage. We showed that an oligopeptide (peptide 1 in Table I) representing the cleavage site in p66 of HIV-1 for generating the p51 subunit of the heterodimeric reverse transcriptase of HIV-1 and another peptide (peptide 2 in Table I) representing the homologous sequence in p68 of HIV-2, and therefore proposed to be the cleavage site (22), were substrates of the HIV proteinases (15). These peptides, which match type 2 cleavage site sequences, were the starting points for our design of palindromic substrates since they are partly symmetric with aromatic amino acids at the P 1 , P 1 Ј, and they contain negatively charged residues at the P 3 and P 3 Ј positions.…”
Section: Substitution Of Amino Acids Of a Type 1 Cleavage Site Peptidmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the viral context, the NC-p1 cleavage site is the slowest (50), final (37,54), and, therefore, rate-determining site in HIV-1 Gag to be processed by the viral protease (6,37). NC-p1 has a polar Asn at the P1 position, while a hydrophobic or aromatic residue is found at the same location in the other substrate sequences.…”
mentioning
confidence: 99%